Acrocomia aculeata (Jacq.) Lodd. ex Mart. (Arecaceae) no Norte de Minas Gerais: morfoanatomia de flores e frutos e aspectos da biologia reprodutiva - Hellen Cássia Mazzottini dos Santos (2012)
Acrocomia aculeata is a palm economically important, especially for the potential of oleaginous fruit. The objective was to conduct the study morfoanatômico of flowers and fruits, and addressing aspects of the reproductive biology of A. aculeata. The study was conducted in four populations of A. aculeata located in the northern state of Minas Gerais, Brazil. The inflorescence length and rachilles was measured and determined the number, fresh weight and dry weight of flowers pistillate and staminate on 20 rachilles each region panicle (basal, middle and apical). The evaluation was performed in morphoanatomical flowers and fruits throughout the development. We used standard procedures in plant anatomy, scanning electron microscopy and histochemical tests. Flowers are trímeras despite the staminate triad submit additional petals, and there is great morphological variability influenced the area, and individual position in the inflorescence. Perianth thick fiber bundles, stegmatas, containing phenolic idioblasts, raphides, ducts, and trichomes are specialized structures in preventing herbivory. Osmophores present in the corolla and fillets are responsible for releasing odors that attract pollinators. The transition to monoicia is evidenced by the occurrence of staminate flowers with well developed ginecel sterile and ovules hemianátropos. The fruit demand about 360 days for the development, which has three phases: histodifferentiation pericarp, seed maturation and ripening of mesocarp. The female flowers are tricarpelares, but usually only one egg develops into seed; others egg degenerate and become involved by endocarp lato sensu. The embryo is differentiated to 130 days after flowering. The plate pore originates locular epidermis and is the endocarp strict sense. The exocarp is the first structure to achieve maturation, followed by seed. The endocarp is lignificando continues until close to abscission. The mesocarp initiates the deposition of lipids at about 345 days after anthesis and shows no signs of maturation, suggesting possible climacteric behavior.